Philosophical and psychological foundations of pedagogical conception of Stephan Balei (1885-1952) - Nataliia Fanenshtel (Vasyl Stefanyk Precarpathian National University, 2017)
Through the analysis of S.Balei's scientific papers philosophical and psychologicalbases of his pedagogical concept has been explored. In particular, revealed the influence ofhumanistic-anthropological ideas of the end of XIX beginning of XX century on thephilosophical views of the scientist and role of Professor K.Tvardovsky and traditions of theLvov-Warsaw Philosophical School. The need for a comprehensive study of the pedagogicalideas of S.Balei is caused by their relevance for the construction of the national system ofeducation in Ukraine. Key words: psychotechnics, educational contact, psychology education (educationalpsychology), psychology of adolescental age, social psychology.